Comparison of Gene Expression Profiles in Human Germinal Vesicle Before and After Cytoplasmic Transfer From Mature Oocytes in Iranian Infertile Couples - Fatemeh Sadat Hoseini; Nasser Salsabili; Firoozeh Akbari-Asbagh; Reza Aflatoonian; Seyed Hamid Aghaee-Bakhtiari (Tehran University of Medical Sciences, 2016)
Objective: To evaluate the effect of cytoplasm transfer from mature oocytes to germinal vesicle(GV)s on promoting the maturation of cytoplasm of GV at the mRNA level. Materials and methods: Sixty six in vitro fertilization (IVF) operations between June 2012 and November 2013 were included in this study. Totally 120 GVs were obtained. Normal GVs were categorized into 3 groups (n = 40) randomly: the first comprised oocytes that did not receive the cytoplasm of mature oocytes; the second group comprised oocytes that did not receive the cytoplasm of mature oocytes but were incubated for 24 h; and the third group comprised oocytes that received 10-15% the cytoplasm of mature oocytes and were then incubated for 24 h. Each group was separately analyzed by quantitative polymerase chain reaction (qPCR) and the expression levels of selected genes were assessed. Results: The expression levels of genes involved in the cytoplasmic maturity, and energy-producing mitochondria were significantly higher in the pooled oocytes of 2nd control group than those of the 1st control and intervention groups (p < 0.001). The genes involved in the meiosis, spindle check point, DNA repairing and cell cycle checkpoint did not have any expression in the 1st and intervention groups; however, these genes were expressed in the 2nd group, significantly. In the 2nd group, the highest expression level was observed for genes involved in the DNA repairing and cell cycle checkpoint. In the intervention group, none of the genes were expressed except for energy-producing mitochondria gene; even in this case, the expression level of this gene in this group of oocytes was significantly lower than that in other groups (p < 0.001). After 24 h meiosis assumption was significantly higher in the third group than in the second group (95% vs. 68%, p < 0.001). Conclusion: The cytoplasm transfer technique is not effective in cytoplasmic maturity of the recipient GV oocytes. In contrast, 24-hr in-vitro culture is associated with increased expression of studied genes in GVs.